Up-Regulating ERIC by CRISPR-dCas9-VPR Inhibits Cell Proliferation and Invasion and Promotes Apoptosis in Human Bladder Cancer - Yang, Jiangeng; Xia, An; Zhang, Huajie; Liu, Qi; You, Hongke; Ding, Daoyuan; Yin, Yonghua; Wen, Bo (Frontiers in Molecular Biosciences, 2021)
LncRNAs are defined as non-coding RNAs that are longer than 200 nucleotides in length. The previous studys has shown that lncRNAs played important roles in the regulation of gene expression and were essential in mammalian development and disease processes. Inspired by the observation that lncRNAs are aberrantly expressed in tumors, we extracted RNA from Bladder urothelial carcinoma and matched histologically normal urothelium from each patient and bladder carcinoma cell lines.Then,we reversed transcribed them into cDNA .Last,we investigated the expression patterns of ERIC by the fluorescence quantitative PCR in bladder cancer tissues and cell lines. CRISPR-dCas9-VPR targeting ERIC plasmid was transfected into T24 and 5637 cells, and cells were classified into two groups: negative control (NC) and ERIC overexpression group. MTT assay, transwell assay, and flow cytometry were performed to examine changes in cell proliferation, invasiveness, and apoptosis. We found that the expression of ERIC was down-regulated in bladder urothelial carcinoma compared to matched histologically normal urotheliam. The differences of the expression of this gene were large in the bladder cancer lines. Compared with the NC group, the ERIC overexpression group showed significantly decreased cell proliferation rate (t = 7.583, P = 0.002; t = 3.283, P = 0.03) and invasiveness (t = 11.538, P <0.001; t = 8.205, P = 0.01); and increased apoptotic rate (t = −34.083, P <0.001; t=−14.316, P <0.001). Our study lays a foundation for further study of its pathogenic mechanism in bladder cancer.